KINERJA KARYAWAN BAGIAN AKUNTANSI DENGAN DIMENSI TEKNOLOGI AKUNTANSI (Studi Pada Bank Perkreditan Rakyat di Karanganyar) - Sapariyah, Rina Ani; Wahyudi, Ridwan; Setyorini, Yanti (-)
This research aims to provide empirical evidence of significance performance of Accounting Department with Dimention of Accounting Technology with variabel of  effect of use information technology , effectiveness of accounting information system , task conformity and internal control System to employee performance (study at Rural Banks in Karanganyar District). The data obtained in the form of primary data from 7 BPRs in Karanganyar District. The population in this research is employees of accountancy / finance, credit admin, teller and customer service that use information technology and accounting information system in completion of its work at the Rural Bank in Karanganyar Regency. Sampling using purposive sampling method. The number of samples collected was 80 respondents. Test instruments used in this study using the test reliability and validity test. Classic assumption test consisting of normality test, multicolinearity and heteroskedastisitas, while for testing hypothesis in this research using multiple linear regression test, t test and coefficient of determination test (Test R2). The results of the classical assumption test show that this study is normally distributed, Does not occur multicolinearity and does not occur heteroscedasticity . The result of the analysis testing shows that the variable use  of information technology has a positive and significant effect on employee performance, the effectiveness of accounting information system has a positive and significant effect to employee performance and conformance task  has a positive and significant impact to employee performance. The result of determination coefficient test (Test R2) independent variable able to explain the dependent variable equal to 42,9% while the remaining 57,1% influenced by other factor not examined.Keywords:   Use   Of   Information  Technology,  Effectiveness  Of  Accounting  Information  System, Task  Conformity,   Internal  Control  System,  Employee Performance.